Contours of agency : essays on themes from Harry Frankfurt - Buss, Sarah; Overton, Lee (Bradford book., 2002)
The original essays in this book address Harry Frankfurt's influential writing on personal identity, love, value, moral responsibility, and the freedom and limits of the human will. Many of Frankfurt's deepest insights come from exploring the self-reflective nature of human agents and the psychic conflicts that self-reflection often produces. His work has informed discussions in metaphysics, metaethics, normative ethics, and action theory. The authors, recognized for their own contributions to the understanding of human agency, defend their original philosophical positions at the same time that they respond to Frankfurt's. Each essay is followed by a response from Frankfurt, in which he clarifies and elaborates on his views.